PERAN HUKUM TATA NEGARA ADAT KALILI “TONDA TALUSI” DALAM PENGUATAN MODERASI BERAGAMA DI LEMBAH PALU - Randy Atma R Massi; Mursyid, Besse Tenriabeng (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
Palu City is the capital of Central Sulawesi Province. The original inhabitants of Palu City are the Kaili tribe. Most of the population adheres to Islam (86.99%), Christianity (10.65%), Catholicism (0.90%), Hinduism (0.93%), Buddhism (0.50%), and Confucianism (0.001%). The potential for diversity certainly contains both positive and negative values. Conflicts due to ethnic and religious diversity often occur. What is interesting is that the largest tribe in the Palu Valley, which has an open character with differences and diversity, is the character of the Kaili people, so this is interesting to study, especially regarding the abilities of the Kaili tribe with its system called